A study on wild rats and their endoparasite fauna from the Endau Rompin National Park, Johor - A.S.K, Syed-Arnez; S.N, Mohd Zain (Malaysian Journal of Science, 2006)
A survey of the Endau Rompin National Park’s wild terrestrial rats and related helminth parasites was carried out to determine the current population and biodiversity. A total of 128 rats were trapped, identified and examined for endoparasites. Prevalence and mean abundance of different parasites were calculated. A total of eight rat species were identified, namely, Leopoldamys sabanus, Maxomys rajah, Maxomys surifer, Maxomys whiteheadii, Rattus exulans, Rattus rattus diardii, Rattus tiomanicus and Sundamys muelleri. Endoparasite fauna recovered from all rats consists of 23 nematode species (Angiostrongylus malaysiensis, Capillaria hepatica, Cyclodonstomum purvisii, Filarioidea fam. gen. sp., Globocephalus connorjilii, Gongylonema neoplasticum, Heligmonoides bulbosus, Heterakis spumosa, Mastopharus muris, Macrostrongylus ratti, Malaystrongylus odontospicularis, Maxomystrongylus sp., Nippostrongylus brasiliensis, Orientostrongylus sp., Paraheligmonelloides sp., Physalopteridae gen. sp., Rattustrongylus odontoconus, Rattustrongylus rotundoconus, Reticularia tanii, Strongyloides ratti, Strongyloides venezuelensis, Subulara andersoni, and Syphacia muris), three cestode species (Hymenolepis diminuta, Rodentolepis nana and Taenia taeniaformis), two trematode species (Fibricola ramachandrani and Zonorchis sp.) and one pentastomide species (Armillifer moniliformis). Overall prevalence was 90.63% with Heligmonellidae parasites being the dominant helminth. New rat hosts of several parasites were also identified. Changes in the types of parasites between the present survey and an earlier study of the same area are believed to have been caused by the intrusion of commensal rats, particularly Rattus tiomanicus, into the park. The current qualitative composition of rats and related endoparasites can be attributed to the ongoing human activities at the park. Therefore it is the aim of the present study to provide the much needed baseline data to design an appropriate programme for environmental monitoring and biomedical research within the park.